(3GdCQcGfs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3bGd LGHQ Ydjg GdQMeI (B: (3ajg MLQ GdadGSaI hJOHjQg hNhGUg ajfHZi Cf JYde Cf MLQ GdadGSaI dGjchf EdG ef GdMjhGf s
(3BNQgG (B:s
(3aEPG CQOJ GdYed Jdbi efg hGMO Ydi CQHY hYTQjf beQ jbhe TeSkG HEPf Gddg JYGdi Hefg hcQeg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B105s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B95 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdaGJM (B(5309) s
Keywords: (3GdcjejGA h GdWHjYjGJs